The Role of Political Communication in Shaping Public Opinion: A Comparative Analysis of Traditional and Digital Media - Rollyn Sofyan Daud (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The purpose of this cross-media analysis was to better understand how public opinion is influenced by political communication, and how it can be regulated and held accountable to better reflect political discourse in the media. A content analysis of news articles and social media posts, as well as surveys and a review of the pertinent literature, were used to collect data. Traditional media continue to play a significant role in influencing public opinion, but digital media have become a formidable tool for political communication, particularly among newer generations. Concerns regarding the propagation of false information and the impact of social media algorithms impede open and objective political discourse. There was unanimity that regulatory and accountability measures, such as media literacy programs and disclosure requirements for political advertisements, were required to ensure an honest and balanced media portrayal of political debate. These findings highlight the need for ongoing research and policymaking to address the dynamic character of political communication in the digital age.